Chemical, technological, and sensory quality of pasta and bakery products made with the addition of grape pomace flour - Boff, Jaqueline Menti (2022)
Grapes are one of the most cultivated fruits in the world. Concomitantly, a large amount of waste is generated from this product. Grape pomace (GP) flour can be used as an increment for making new food products. GP is rich in fibers and phenolic compounds, and in addition could be used to reduce agro-industrial residues. Thus, the objective of this study was to evaluate the influence of the addition of different percentages of grape pomace (GP) on the chemical, technological, and sensory characteristics in pasta and bakery products. An integrative review was conducted. The selection of papers was carried out by searching studies in databases. An improvement in chemical quality with the addition of GP was observed, such as fiber, anthocyanin, and micronutrient content. Biscuits, cookies, cakes, breads, and pasta did not show any impairment in terms of acceptability. However, biscuits and cookies had the best global acceptance. The degree of acceptance still seems to be low for the use of GP to be included in high quantities in successful products. Samples with a maximum of 10% addition of GP flour seem to be accepted. On the other hand, the higher the percentage of GP flour, the healthier benefits they seem to promote.